THE ROLE OF SUSTAINABLE MARKETING IN IMPROVING EMPLOYEE PERFORMANCE IN TOURISM COMPANIES -AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF CUSTOMERS OF TOURISM COMPANIES IN THE HOLY CITY OF KARBALA - Ahmed Naji Hussein; Abeer Mohammed Mahdi AL-shammari; Ali Fadhil Jebur Al-yousfe (Scholars Digest Publishing, 2024)
The current research is interested in studying the nature of the relationship between the two variables (sustainable marketing and employee performance) in tourism companies in the holy city of Karbala. The research hypotheses were built on the basis of the nature of the correlation and influence relationships between the independent variable and the dependent variable. The study tool, which is the questionnaire, was adopted to present a group From the questions asked to the research sample and obtaining adequate answers to achieve the research objectives, and in light of the research problem, the researchers were interested in interpreting the sample’s answers statistically through the statistical program SPSS and arriving at results that serve tourism organizations and emphasizing the role of sustainable marketing in supporting the goals and requirements of employees and directly influencing their performance in Companies.
Keywords: sustainable marketing, ability and desire, societal engagement, tourism companies, employee performance.